Analysis of aiming technique in archery shooting - Mohd Zulhilmi, Abd Jabar (2013)
This thesis presented about analysis of aiming technique in archery shooting for the enhancement of archery sports in Malaysia. Before this, engineering in sport was not popular as many people did not realize the important of engineering factors in sports. It was not discovered and most of the athletes depend on the experienced and their practice in order to achieve their target. This study will be focusing on the aiming part and the factors that will affect the aiming and concentration of the archery athletes. Based on this study, there are a few factors that will be determined to be the cause for the distraction of the aiming phase. Corresponds to the project background and problem statements, it is decided that the objectives of the project are to analyse the aiming techniques from archery athletes, to study the relationship between the heart rate and emotions with the performance and to relate the aiming time with the shot points. The results from the analysis of heart rate proved that lower heart rate will distribute to a higher score. From the biofeedback device, the emotions level showed a distraction to the performance of the athletes. The increase of stress level can cause a lower accuracy during the aiming phase and will distribute to a lower score. For the aiming time, three parameters have been set up which are 3, 5 and 7 seconds. From this aiming time, the best total score is during the aiming time in 5 seconds.